Can memory training positively affect the skills of learning a foreign language and support learning English by older students? : Experiment conducted at the University of Third Age at the University of Wrocław - KOZAK, AGATA; GULANOWSKI, JACEK (Journal of Education Culture and Society, 2020)
The experiment covered in this paper was conducted from November 2011 until Febru-ary 2012 in the University of Third Age at the University of Wrocław in Poland as a part of the Third Age and New Technologies (TANT) project which was realised as a Grundtvigpartnership programme. The aim of the experiment was to determine whether memory training can positively affect learning a foreign language (English) by senior students.